Comparisons of Energy Efficiency Management Techniques in Cloud Based Environment - et. al., Krishan Tuli , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud computing has been transforming large part of various IT services into virtualization which are made available as a utility services and scheduling plays a vital role here to get maximum utilization from various physical resources. Cloud Computing has been offering its virtual resources and services anywhere and anytime on pay-as-you-go basis. So, Cloud Computing becomes a backbone in the various fields of Industry and Academia for providing the storage backups, load balancing and most importantly providing the dynamic resource scheduling on a real-time basis. Therefore, energy consumption will be very high by the various clod data centers which lead to very high amount of operational cost and harm the environment as well. Hence, there is a requirement of Green Computing for the sustainability and ensuring the energy efficiency by energy efficient techniques. In present scenario, various energy efficient algorithms have been proposed by the researchers which reduce the energy efficiency of cloud environment. But all these algorithms have been evaluated using the same experimental environment which gives the related results and it becomes difficult for the researchers to choose the best algorithm among them. So to provide the better understanding on the various algorithms and helps researchers for choosing the best suitable algorithm, we have compared the various state of art energy efficient algorithm in more detailed way considering various prospective. Along with the comparison, we have also done studied the overview of investigated algorithm. Finally, we have the literature survey of various others related to different parameters and techniques. From the same literature survey, we have come to the conclusion of each author’s statement.